2014
DOI: 10.1002/pd.4382
|View full text |Cite
|
Sign up to set email alerts
|

NIPT: current utilization and implications for the future of prenatal genetic counseling

Abstract: Background Non-invasive prenatal testing (NIPT) for select fetal trisomies became clinically available in 2011.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…In addition, the cost of NIPT was highly variable and several clinicians suggested that high test costs were limiting implementation and precluding equity of access [3 & ]. Several professional bodies have released guidance on NIPT [52][53][54][55][56] and research with health professionals offering NIPT in the United States shows that this test is largely being implemented according to professional guidelines [17,18,57]. However, a cause for concern was evidence that NIPT is being offered as a diagnostic test by a significant portion of providers [17,57] demonstrating that continuing health professional education and training is essential.…”
Section: Service Deliverymentioning
confidence: 99%
“…In addition, the cost of NIPT was highly variable and several clinicians suggested that high test costs were limiting implementation and precluding equity of access [3 & ]. Several professional bodies have released guidance on NIPT [52][53][54][55][56] and research with health professionals offering NIPT in the United States shows that this test is largely being implemented according to professional guidelines [17,18,57]. However, a cause for concern was evidence that NIPT is being offered as a diagnostic test by a significant portion of providers [17,57] demonstrating that continuing health professional education and training is essential.…”
Section: Service Deliverymentioning
confidence: 99%
“…For example, while most IC recommended confirmatory diagnostic testing for screen-positive results and some IC strongly emphasized that cfDNA screening is not diagnostic, nearly a quarter of IC never used the phrases “not diagnostic,” “screen,” or “screening test” to describe cfDNA screening. Explanations that cfDNA is not diagnostic are particularly important, given reports that many women misunderstand cfDNA screening results to be diagnostic and may even terminate without confirmatory testing (37, 48). Such misunderstandings might also be lessened by clear expectations regarding screening results, but many IC in our sample did not explain how results would be presented, to whom they would be provided, and/or that results can be incorrect.…”
Section: Discussionmentioning
confidence: 99%
“…The information parents are offered about genetic conditions should be up-to-date, accurate, and balanced—particularly because potential parents make termination decisions against a backdrop of consistent societal bias against those with disabilities (32–34). Evidence suggests that cfDNA screening could lead to increased pregnancy terminations (35, 36); indeed, nearly 15% of surveyed genetic counselors indicated they had at least one patient terminate a pregnancy in their clinic based on cfDNA screening results alone (37). Bias concerning disability, both among health care providers and in public opinion, may influence such decisions (38–41).…”
Section: Introductionmentioning
confidence: 99%
“…29 This has fueled concerns that more women will be making decisions with insufficient education concerning the risks, benefits and limitations of various available options. 61, 62 Patients and clinicians are drawn to cell free DNA screening because of the greater detection for trisomy 21 compared with conventional maternal serum and ultrasound screening. 63, 64 However, implementation of cfDNA screening has been driven in part by market forces rather than a thoughtful integration into current test offerings.…”
Section: Non-invasive Prenatal Screening (Nips) For Fetal Aneuploidiementioning
confidence: 99%